Effect of shear ratio on rheological properties of suspension in two-step flocculation process for fine iron tailings - Yang, Ying; Wu, Aixiang; Wang, Xiancheng; Wang, Guoli (Frontiers in Materials, 2023)
In the two-step flocculation process, shear has a significant impact on the rheological properties of the flocculating slurry. In this study, the orthogonal experiments of two-step flocculation process for fine iron tailings were designed. Based on the change of shear ratio, different shear rates and shear time were designed, the yield stress, plastic viscosity and maximum packing fraction of the flocculated suspension in each group were measured and calculated with a rheometer. The result of range and variance analysis shows the shear rate in the primary broken phase was the biggest factor affecting the yield stress and plastic viscosity of the flocculated slurry in two-step flocculation process. When the shear rate increased from 100 s-1 to 400 s-1, the yield stress and the plastic viscosity of the flocculated slurry increased by 7.14% and 21.30%, respectively. When the shear rate changed from 400 s-1 to 800 s-1, they decreased by 23.27% and 33.17%, respectively. Since the shear ratio in a two-step flocculation process is also related to both shear action and floc structure parameter, the shear ratio was introduced into the first-order reversible kinetic rate equation. Through establishing the relationship between the shear ratio and the floc structural parameter of flocculating suspension, a theoretical model of the shear-dependent maximum packing fraction was established. The measured values and theoretical calculated values of the maximum packing fraction in two-step flocculation experiments were in good agreement and the error was within 5%. Last but not least, the internal mechanism of the theoretical model was discussed from the microscopic point of view.